Age Gender and Education Dependent Alterations of Handwriting and Signature - Alkan, Nevzat; Fincancı, Şebnem Korur; Arıcan, Nadir; Kurtaş, Ömer (The Bulletin of Legal Medicine, 1996)
Alterations in handwriting is mostly seen in elder period. In this study, features of signature and handwriting are investigated in randomly sized groups composed of old and young subjects. For this reason, some parameters such as vertical lines, horizontal lines, left and right space, handwriting, writing speed, increase in space between letters, mistakes in copying, the similarity of the first and last signature and signature matchings are used. Decrease in writing speed, increase in the interspace of letters, increase of handwriting and signature length, decrease in readibleness are found in the group of old subjects. Evaluation of the group without education revealed the horizontal lines, punctuation constancy and the similarity of the first and last signature to be distorted. In the same manner, the signature length was found to be increased and signature uniformity was absent in this group. In practice of forensic medicine, the decrease in writing speed, increase in spaces between two letters are important for detection of copied writings and signatures. The age of subject is important for age dependent alterations of handwriting and signature. Keywords: Handwriting, Signature, Ageing, Forensic document examination, Graphology